Can gases behave like explosives: Large-scale deflagration to detonation testing. (September 2017) - Davis, Scott; Engel, Derek; van Wingerden, Kees; Merilo, Erik
A large vapor cloud explosion followed by a fire is one of the most dangerous and high consequence events that can occur at petrochemical facilities. However, one of the most devastating explosions is when a deflagration transitions to a detonation, which can travel at speeds greater than 1800 m/s and pressures greater than 18 barg. This phenomenon is called a deflagration-to-detonation transition, whereby the deflagration (flame front) continues to accelerate due to confinement or flow-induced turbulence (e.g. obstacles) and ultimately transitions at flame speeds greater than the speed of sound to a detonation. Unlike a deflagration that requires the presence of confinement or obstacles to generate high flame speeds and associated elevated overpressures, a detonation is a self-sustaining phenomenon having the shock front coupled to the combustion. Once established, the resulting detonation will continue to propagate through the vapor cloud at speeds (1800 m/s) that are of similar order as high explosives (7000–8000 m/s). While there are differences between high explosives and vapor cloud explosions (e.g. high explosives can have pressures well in excess of 100 bar), vapor cloud explosions that transition to detonations can cause significant damage due to the extremely high pressures not typically associated with gas phase explosions (>18 barg), high energy release rate per unit mass, and higher impulses due to large cloud sizes. While the likelihood of deflagration-to-detonation transitions is lower than deflagrations, they have been identified in some of the most recent large-scale explosion incidents. The consequences of deflagration-to-detonation transitions can be orders of magnitude larger than deflagrations. This article will present the results of large-scale testing conducted in a newly developed test rig of 1500 m 3 gross volume involving stoichiometric, lean, and rich mixtures of propane and methane.